Genetic dismemberment of Retinal Dystrophies and Hereditary Optic Neuropathies in Morocco and North Africa : Clinical and Genetic spectrum in North Africa : analysis of 5 Genes (ABCA4, CRB1, PDE6B, TTLL5 and ND4) in 6 Moroccan families - (:unkn) unknown (My University, 2022)
Inherited retinal dystrophies (IRD) and optic neuropathies (ION) are the two major causes world- wide of early visual impairment. First, in order to studies Moroccan families with IRD and ION, we recruited 6 families (4 IRD and 2 ION). In the two ION families, we identified the mtDNA variant (m.11778G>A) in a homoplasmic state, linked to Leber's ION phenotype (LHON). This represents the first characterization of this disease in Morocco, and in North Africa. In the four IRD families, we identified homozygous and heterozygous compound variants in CRB1, PDE6B, ABCA4 and TTLL5. These IRD families represent the first ones described in Morocco. Secondly, we compiled data from 413 North African families with IRD and ION. We found that IRD (82.8%) are more frequent than ION (17.2%), and IRD are mainly represented by retinitis pigmentosa and Usher syndrome. ION were identified in 71 families, most often with a syndromic presentation (84.5%). Non-syndromic ones were reported in only 11 families with autosomal recessive optic atrophies related to OPA7 and OPA10 variants, or with LHON linked to mitochondrial variants. Overall, consanguinity has a major impact in the North African countries. Moreover, we have identified many founder variants within small endogamous communities. Altogether, this work contributes to the improvement of the molecular diagnosis of these pathologies in Morocco and North Africa.
Keywords: African Research